Efektivitas Efepoetin Alfa dalam Mengatasi Anemia yang Disebabkan oleh Kemoterapi pada Pasien Kanker Payudara: Serangkaian Kasus: Laporan Kasus - Abidin, Zainal; Fatimah, Anova (Cermin Dunia Kedokteran, 2025)
Introduction: Anemia is a common complication among cancer patients and substantially reduces quality of life (QOL) through symptoms such as fatigue and cognitive impairment. This case evaluates the use of efepoetin alfa to treat chemotherapy‑induced anemia (CIA) in late‑stage breast cancer patients in Indonesia. Case: Six Asian women aged 43–59 years with stage III breast cancer receiving docetaxel‑doxorubicin chemotherapy developed moderate anemia (mean baseline hemoglobin [Hb] 9.5 g/dL). Patients received subcutaneous efepoetin alfa (generally 0.3 mg/0.3 mL once); Hb was reassessed at an average of 8 days after the last injection. Discussion: Post‑treatment mean Hb rose to 12.1 g/dL (mean ΔHb ≈ 2.6 g/dL). No serious adverse events were observed during the short follow‑up. Conclusion: In this case, efepoetin alfa was associated with rapid increases in Hb and improved patient‑reported outcomes; however, a confirmatory larger study, standardized dosing and monitoring, and longer follow‑up are required to define efficacy and long‑term safety.